2021
DOI: 10.21037/jtd-2019-ipicu-09
|View full text |Cite
|
Sign up to set email alerts
|

An evolving role for endobronchial ultrasonography in the intensive care unit

Abstract: Endobronchial ultrasound (EBUS) bronchoscopy is an established minimally-invasive modality for visualization, characterization, and guidance of sampling of paratracheal and parabronchial structures and tissues. In the intensive care unit (ICU), rapidly obtaining an accurate diagnosis is paramount to the management of critically ill patients. In some instances, diagnosing and confirming terminal illness in a critically ill patient provides needed closure for patients and their loved ones. Currently available da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Relevant studies have shown that the lung ultrasound score has a high diagnostic efficiency in detecting novel coronavirus pneumonia in patients with ARDS and can be used as an important reference index for diagnosis ( 25 - 27 ). Besides, endobronchial ultrasonography has been successfully used in the ICU and helped clinicians to better understand and treat bronchial problems ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown that the lung ultrasound score has a high diagnostic efficiency in detecting novel coronavirus pneumonia in patients with ARDS and can be used as an important reference index for diagnosis ( 25 - 27 ). Besides, endobronchial ultrasonography has been successfully used in the ICU and helped clinicians to better understand and treat bronchial problems ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Approaches to these LNs require overcoming the challenges of limited mobility due to the combination of ultrasound bronchoscopes and needles. Some LNs were difficult to approach with the conventional ultrasound bronchoscope, but since the advent of the newer bronchoscope, the miniaturization of the ultrasound tip and the modified puncture angle have improved this situation considerably ( 31 , 32 ). Nevertheless, although it is currently almost impossible to approach the intrapulmonary LNs, a prototype ultrasound bronchoscope with an even thinner tip has been reported ( 33 ), which should make the approach feasible in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The advances in technology have introduced more indications and capabilities to the flexible bronchoscopy. Endobronchial ultrasonography, 1 cryotherapy, 2 and airway stents 3 are few examples.…”
Section: Introductionmentioning
confidence: 99%